Didactic strategy as an innovative resource to promote the concepts of peace and coexistence in school. (Revista Investigación & praxis en CS Sociales, 2022)
Educational modernization comprises a set of adaptive strategies from various instances and centers of power, aimed at rationalizing education from the perspective of systemic dwelling, so that educational systems are organized in line with the changing objectives imposed by the process of evolution and development in global society. In accordance with the above, there are some of the foundations and roots on which the tree of education must be sustained, so that under its shade, children, youth, and adults can find shelter for valuable education. In correspondence with the aforementioned, the purpose of the research work is stated: To design a didactic strategy as an innovative resource to promote the concepts of peace and coexistence in school with 11th-grade students of the José Eustasio Rivera Educational Institution in the Municipality of Saravena, Colombia. Based on the purpose of the study, its aim is to guide teachers with didactic strategies that enable them to guide the student population in addressing the violence problems they face in school.
Keywords: Educational modernization; didactic strategy; onceptions of peace and coexistence